Identification and characterization of a Relish-type NF-κB, DvRelish, in Dermacentor variabilis in response to Rickettsia rickettsii infection - Fongsaran, Chanida; Verhoeve, Victoria I.; Jirakanwisal, Krit; Harris, Emma K.; Macaluso, Kevin R. (Frontiers in Cellular and Infection Microbiology, 2024)
Ixodid ticks serve as hosts and transmission vectors for several obligate intracellular bacteria, including members of the spotted fever group (SFG) of Rickettsia. Although ticks generate an immune response to bacterial insults, many of the signaling molecules associated with the response and how they may contribute to vector competence for Rickettsia are undefined. In this study, we isolated a full-length dvrelish transcript from Dermacentor variabilis, which encoded a Relish-type NF-κB. The presence of a canonical Rel homology domain (RHD) consistent with NF-κB proteins suggested a role in tick immune response for DvRelish. The expression of DvRelish was confirmed in tick tissues and fluorescent microscopy of tick hemocytes indicated increased expression following infection with Rickettsia as compared to a non-tick-borne bacterial pathogen. To further determine the effect of dvRelish gene knockdown on rickettsial infection, we used RNA interference-mediated gene knockdown in D. variabilis and demonstrated that transcription of dvRelish was decreased after 24 h post-injection of siRNA. We then assessed the response of D. variabilis when exposed to Rickettsia rickettsii and determined that transcription of dvRelish was inversely associated with rickettsial loads at 48 h post-exposure. Further studies are required to broaden the understanding of differential immune responses in ticks to SFG Rickettsia infection and elucidate the role played by the arthropod immune system in vector competence.